2017
DOI: 10.1111/aogs.13186
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing levator‐ani muscle stiffness pre‐ and post‐childbirth in European and Polynesian women in New Zealand: a pilot study

Abstract: Quantification of levator-ani muscle stiffness is feasible. Muscle stiffness is significantly different before and after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
21
1
1
Order By: Relevance
“…Other groups have developed devices that improve the reliability of the measurement of intravaginal pressure, laxity of the vaginal wall, and mechanical strain but these devices do not address the entire vaginal wall simultaneously …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have developed devices that improve the reliability of the measurement of intravaginal pressure, laxity of the vaginal wall, and mechanical strain but these devices do not address the entire vaginal wall simultaneously …”
Section: Introductionmentioning
confidence: 99%
“…6 Other groups have developed devices that improve the reliability of the measurement of intravaginal pressure, 7-10 laxity of the vaginal wall, [11][12][13][14] and mechanical strain but these devices do not address the entire vaginal wall simultaneously. 15,16 Localized measurements of the mechanical properties of vaginal tissue in vivo using skin elasticity 13,14 have revealed reduced elastic modulus in women with POP compared to women with normal vaginal support. This device measured the deflection of tissue in response to a slight vacuum applied over a small area of the vaginal wall.…”
mentioning
confidence: 99%
“…Briefly, the patient was first instructed to perform a maximum voluntary contraction of her perineal muscles whilst the PFM was palpated clinically to determine the optimal placement of the speculum at the level of the PFM. Following insertion of the speculum in the closed position, the device was opened in 10mm stepwise increments to a maximum tolerated aperture of 40 mm (which demonstrated high reliability in preliminary studies), slightly lower than previously reported [17] as some women with OASI could not tolerate the 50-mm aperture. At each step, force measurements were acquired over 1 s after a 3-s relaxation time.…”
Section: Vaginal Elastometrymentioning
confidence: 95%
“…Stiffness values are quantified in Newton/m (N/m). The portable device prototype is highly acceptable, consistent and repeatable in both non-pregnant and pregnant women [17]. The measurements were carried out by a single trained operator-the research nurse/midwife-employing a predefined protocol as previously described [17].…”
Section: Vaginal Elastometrymentioning
confidence: 99%
See 1 more Smart Citation